Azithromycin concentration in severely inflamed canine external ear canals – a case series. (26th July 2020) - Perry, E.; Lavy, E.; Soback, S.; Britzi, M.; Zur, G.
Abstract : Objective: To determine azithromycin concentration in severely inflamed canine external ear canals. Material and Methods: Five dogs of various breeds and ages with severe and chronic otitis externa underwent ear canal reconstruction surgery. A single oral dose of azithromycin at 10 mg/kg was administered 12 to 24 hours prior to surgery. Tissue samples were collected from the excised external ear canals and azithromycin concentration was determined using a liquid chromatography‐tandem mass spectrometry method. Results: Azithromycin concentrations ranging from 11.4 to 107.0 μg/g (mean 59.2 ± 44.6 μg/g, median 50.9 μg/g) were detected in the chronically infected external ear canal tissue 12 to 24 hours after administration. Clinical Significance: Little information exists on antibiotic concentrations in pathological tissues of dogs. Macrolides are known to concentrate in skin tissue. In light of the present results, investigation of clinical efficacy of azithromycin in chronic canine otitis externa is warranted.